Stigma, Health Literacy, and Treatment-Seeking Behavior among Caregivers of Stunting Toddlers in Rural Areas - Adella Risma Triwijayanti; Indanah Indanah; Muhamad Jauhar (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Stunting is a health problem that threatens human quality and the competitiveness of the nation. This condition has an impact on the physical, mental, and cognitive development of toddlers and increases the risk of disease. There are still many toddlers who are diagnosed with stunting but do not receive treatment. Treatment-seeking behavior is influenced by knowledge, attitudes, stigma, and community beliefs. This research aims to analyze the relationship between stigma and health literacy with treatment-seeking behavior. The research design uses a correlational analytical approach that is cross-sectional. The independent variables are stigma and health literacy, while the dependent variable is treatment-seeking behavior. This research was conducted in the Keling II Community Health Center Working Area, Jepara Regency, in January 2025. The research sample was 100 caregivers of stunted toddlers and was taken using techniques of purposive sampling. The research instrument includes a stigma questionnaire using (SSCI-8), a questionnaire on health literacy using (HLS-EU-Q16), and a questionnaire on treatment-seeking behavior using (GHSQ). Data analysis using chi-square tests. The results of this study show that there is a significant relationship between stigma (p=0.002; r=0.394) and health literacy (p=0.000; r=0.448) with treatment-seeking behavior in caregivers of stunted toddlers. Stigma and health literacy play a role in shaping behavior in seeking health assistance, especially among caregivers of toddlers with stunting in rural areas. There needs to be intervention to reduce negative stigma and increase health literacy so that caregivers of stunted toddlers have the awareness to carry out screening and treat stunting in health service facilities.